ReH2O Water Recycling Resort and Spa - Agoncillo, Juancho M.; Madrid, Dolores Cecilia T. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
"Love is Pure. Love is Absolute." Water is a necessity to start and maintain life and a healthy lifestyle. The lack of it leads to pain, sickness, and even death. The value of water has never been higher than it is now nor will it always be as readily available as it is now. This architectural design research study as a proposed health and wellness development that highlights health benefits and wellness properties of the universal life giving element that is water as well as going into a study on alternative uses and reuses of this natural resource. The study shall develop and details a commercial development offering alternative means of exercise and wellness at the same time housing an industrial standard water treatment facility that would, as presented throughout the study, not only enable the development a self-sustaining water recycling and reuse system but also establish the development as secondary water supplier for the immediate surrounding developments. This would hopefully open doors to further the study into the safe and efficient reuse of water in promoting health and general well-being.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman